2017
DOI: 10.1007/s10459-017-9753-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of various innovative learning methods in health science classrooms: a meta-analysis

Abstract: This study reports the results of a meta-analysis of the available literature on the effectiveness of various forms of innovative small-group learning methods on student achievement in undergraduate college health science classrooms. The results of the analysis revealed that most of the primary studies supported the effectiveness of the small-group learning methods in improving students' academic achievement with an overall weighted average effect-size of 0.59 in standard deviation units favoring small-group l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
2
33
0
2
Order By: Relevance
“…For many years, learning in a group has been described as an effective learning method [23–25]. It has been shown that collaborative learning increases the learning success for cognitive and affective learning objectives, and increases the social competence of learners [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, learning in a group has been described as an effective learning method [23–25]. It has been shown that collaborative learning increases the learning success for cognitive and affective learning objectives, and increases the social competence of learners [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nursing students taking an online course may self-reportedly work harder, and feel more like part of a group, than peers taking a traditional face-to-face course, taught by the same educator (O'Neil & Fisher, 2008). However, such positive outcomes will only be obtained if educators have the required competences in digital collaborative learning (Mikkonen et al, 2019a;Kalaian & Kasim, 2017;Scardamalia & Bereiter, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In alignment with the available literature for preclinical teaching modalities, we hypothesized that a given student would perform better than expected from probability alone when paired with a highperforming student. 13 We also suspected that majority of students would perceive pairing as affecting their evaluations.…”
Section: Introductionmentioning
confidence: 99%